Utility of platelet indices in alcoholic hepatitis: a retrospective study - Vijayakumar, Saravanakumari (Porto Biomed J, 2020)
BACKGROUND: The commonly available platelet indices are platelet distribution width (PDW), plateletcrit (PCT), and mean platelet volume (MPV). They have been used in diagnosis and prognosis of various abdominal disorders. They have never been used to predict severity of alcoholic hepatitis. METHODS: A retrospective analysis of chronic alcohol consumers presenting with jaundice and deranged liver function tests was performed. Maddrey discriminant function (MDF) and modified end-stage liver disease (MELD) scores were calculated and patients compared between severe and nonsevere alcoholic hepatitis (MDF ≥32 vs MDF <32 and MELD >20 vs MELD ≤20). Logistic regression analysis was performed to find significant predictors. Receiver operating characteristic was used to find the area under the curve. Spearman correlation was performed to discover association between platelet indices and severity scores. RESULTS: There were 119 patients in the study. Coexisting illnesses included pancreatitis, cirrhosis, infections, and alcohol withdrawal syndrome. The mean age (years), duration of alcohol consumption (years), and ethanol (g/day) were 45.13 ± 11.53, 18.84 ± 11.40, and 65.61 ± 45.42, respectively. The average MELD and Maddrey scores were 14.13 ± 5.17 and 36.45 ± 29.63, respectively. The mean platelet counts, PDW, MPV, and PCT were 194.01 ± 178.82 × 10(9)/L, 17.10 ± 1.21, 5.99 ± 0.96, and 0.14 ± 0.04, respectively. PDW >18 and MPV had a significant positive correlation with MELD scores. Only bilirubin and prothrombin prolongation were significant predictors of severe alcoholic hepatitis. The area under the curve was highest for PCT at 0.622 (P = .07; confidence interval = 0.500–0.743). CONCLUSIONS: Platelet indices appear to be significantly altered in alcoholic hepatitis, but they do not predict severe disease. Whether this inability to predict severe alcoholic hepatitis is due to coexisting illnesses such as pancreatitis, cirrhosis, and infection needs to be studied further.